(3GdeNJGQ ef TYQ GdHMJQis - (3GdHMJQj , CHh YHGOI GdhdjO Hf YHjO Hf jMji GdWGFj GdHMJQj, GdHMJQj,J (B284 (3g` s
(3ChdgG (B:s
(3Chdg ef bUjOI jeOM HgG CHG SYjO eMeO Hf jhSa GdKZQi RYe GdZQGH efHF GdCfHGA Cf GdCMHI BPfhG HJfG s
(3BNQgG (B:s
(3BNQg eHJhQ jfJgi CKfGA bUjOI eWdYg (B: (3NjGd jYJQjfi ai GdefGe dTcQi GddMX aGJfI GdbhGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3HgG fXGe GdJYbjHIs
(3OjhGf TYQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B9 - (3U (B141s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdCOHs